Microbiology : - Black, Jacquelyn G. (Wiley, 2013)
"Jacquelyn Black's 8th Edition of Microbiology: Principles and Explorations builds upon the previous best-selling textbooks in this series with an enhanced introduction to the study of Microbiology in the same engaging writing style throughout the narrative. The text's is even more reader-friendly and focuses on microbiology, allied health, agriculture and food sciences topics"--